2023
DOI: 10.3390/ijerph20021496
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling between Economic Growth and Carbon Emissions: Based on Four Major Regions in China

Abstract: This paper constructs a decoupling model for four major economic regions of China, based on the Tapio decoupling index method and VAR model for carbon emissions to compare and measure the impact of decoupling between carbon emissions and economic growth in China during 1997 to 2019. The results show that the degree of decoupling between economic growth and carbon emissions varies among different economic regions, and the decoupling status is better in all regions at the beginning of the 21st century. In genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The study identified that economic growth emerged as the primary factor influencing carbon emissions in China, while energy intensity played a more substantial role in the United States. Within a single country, Shen et al [58] divided China into eastern, central, and western regions for their research. Their findings indicated that the energy structure predominantly determined carbon emissions, with a more pronounced impact on the central and western regions than on the eastern regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study identified that economic growth emerged as the primary factor influencing carbon emissions in China, while energy intensity played a more substantial role in the United States. Within a single country, Shen et al [58] divided China into eastern, central, and western regions for their research. Their findings indicated that the energy structure predominantly determined carbon emissions, with a more pronounced impact on the central and western regions than on the eastern regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Referring to the current academic research on the influencing factors of carbon emissions, the main impact factors of carbon emissions in cities and urban agglomerations include economic growth, industry structure, energy consumption, population, technology innovation, and environmental regulation. Most scholars consider that economic growth is the main driver of carbon emission increase, directly affecting the carbon emission intensity from the transportation sector, electricity supply, and other sectors [48][49][50]. Technology innovation can promote the advancement of new energy technologies and the continuous reduction in usage costs, promote the efficient and clean use of coal as well as the green and low-carbon transformation, and significantly increase the proportion of clean energy represented by hydropower, wind power, nuclear energy, and photovoltaic energy, thus continuously promoting the reduction in energy intensity and the optimisation of the energy structure [51,52].…”
Section: System Boundarymentioning
confidence: 99%
“…Therefore, Since GDP is specified as the total value of all completed products and services generated in a particular period, the process is simple: higher GDP means higher production and, consequently, higher carbon emissions. For that reason, Shen et al (2023) highlighted that the decoupling of economic growth and carbon emission lay at the core of sustainable development strategies (Shen et al 2023). Therefore, since the direct relationship between economic growth and carbon emissions impacts automatically affects climate susceptibility in MENA regions, it is crucial to investigate the indirect and integration relationship between economic growth and carbon emissions.…”
Section: The Impact Of Economic Growth On Carbon Emissionsmentioning
confidence: 99%